2015
DOI: 10.1098/rsif.2015.0899
|View full text |Cite
|
Sign up to set email alerts
|

Searching for motifs in the behaviour of larval Drosophila melanogaster and Caenorhabditis elegans reveals continuity between behavioural states

Abstract: We present a novel method for the unsupervised discovery of behavioural motifs in larval Drosophila melanogaster and Caenorhabditis elegans. A motif is defined as a particular sequence of postures that recurs frequently. The animal's changing posture is represented by an eigenshape time series, and we look for motifs in this time series. To find motifs, the eigenshape time series is segmented, and the segments clustered using spline regression. Unlike previous approaches, our method can classify sequences of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…However, behavioural observation shows rather strong similarities in the behavioural modulations resulting from apparently unrelated conditions, such as odour-tastant associative learning and variation of stimulus concentration (Schleyer et al, 2015a), which simultaneously modulate both the klinokinetic and klinotactic responses (weathervaning was not assessed in this study). Also, a recent attempt to categorise larval behavioural states using an unsupervised method based on the animal’s posture suggests the existence of a continuum rather than clear-cut categories (Szigeti et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…However, behavioural observation shows rather strong similarities in the behavioural modulations resulting from apparently unrelated conditions, such as odour-tastant associative learning and variation of stimulus concentration (Schleyer et al, 2015a), which simultaneously modulate both the klinokinetic and klinotactic responses (weathervaning was not assessed in this study). Also, a recent attempt to categorise larval behavioural states using an unsupervised method based on the animal’s posture suggests the existence of a continuum rather than clear-cut categories (Szigeti et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Vogelstein et al (2014) used unsupervised structure learning to infer a hierarchical organization of larval behaviors based on eight time varying measures of posture and motion. Most recently an 'eigenlarva' analysis revealed that many behavioral events defy easy assignment to discrete clusters, suggesting that, at least in larvae, behavior may vary rather continuously (Szigeti et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…How the animal’s posture changes in each of these dimensions is sufficient to explain a wide variety of behaviors, from foraging to thermotaxis[12,13], and has led to the discovery of new behaviors [14] as well as identified novel roles for genes in behavior[15]. Similar approaches that use automated tools to more closely quantify posture have been used to characterize larval zebrafish [16] and larval Drosophila [17] behavior.…”
Section: Automated Methods To Quantify Behaviormentioning
confidence: 99%
“…Converting postures (e.g., ‘straight forearm’ or ‘extended elbow’) into actions (e.g., ‘reaching’) requires some way of clustering together stereotyped sequences of postures that are repeatedly seen with only minor variations. Methods to accomplish this range from embedding postures into a low-dimensional space to find ‘clumps’ of similar sequences[18] to identifying when one posture is predictable from previous postures[19], though other methods exist[15,17,20,21]. What is exciting about these ‘unsupervised’ algorithms is that they offer not only ever-more-precise quantification of what an animal is doing at each moment in time, but also reveal the underlying structure of behavior (e.g., which behaviors are sub-programs of other behaviors or which behaviors co-occur), and offer the potential for discovering completely new behaviors.…”
Section: Automated Methods To Quantify Behaviormentioning
confidence: 99%